Characterization of glycogen-related glycoside hydrolase glgX and glgB from Klebsiella pneumoniae and their roles in biofilm formation and virulence - Liu, Xinyue; Li, Jialin; Wu, Ruibing; Bai, Liping (Frontiers in Cellular and Infection Microbiology, 2024)
Glycogen is a polymer used by bacteria to store excess glucose, playing a crucial role in bacterial growth, stress resistance, biofilm formation, and virulence. In bacteria, the glycoside hydrolase family 13 protein are involved in the synthesis and metabolism of glycogen, respectively. The absence of these enzymes leads to changes in bacterial glycogen content, thereby affecting the growth metabolism of the strain. To date, research on the roles of these glycogen-related glycoside hydrolase genes in the synthesis metabolism and bacterial phenotypes of Klebsiella pneumoniae has been limited. In this study, we characterized the glycogen-related glycoside hydrolase genes glgB and glgX of K. pneumoniae. We found that both enzymes exhibited significant degradation activity against glycogen substrates and were capable of degrading amylopectin, amylose, and pullulan. The optimal temperatures for GlgB and GlgX were both in the range of 35-40°C, with optimal pH values of 7.5 and 7.0, respectively, and they exhibited high stability at 37°C. Subsequently, we deleted the glgB and glgX genes in K. pneumoniae. The deletion of the glgB gene resulted in a decrease in the growth rate of the bacteria and defected glycogen synthesis. In contrast, the deletion of the glgX gene slightly accelerated the growth rate and led to continuous glycogen accumulation. In terms of biofilm formation and virulence, defects in glycogen synthesis impeded biofilm formation and virulence, while continuous glycogen accumulation did not affect biofilm formation but slightly increased virulence. In conclusion, the glgB and glgX genes are essential for the glycogen synthesis and metabolism in K. pneumoniae and further influence the biofilm formation capacity and virulence.